TONGUE REGION BASED DISEASE PREDICTION USING DEEP LEARNING. - P. T., SIVAGURUNATHAN; KAVIYA, S.; JOTHIPRABHA, D.; NANDHINI, M. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Now a days there is a problem and risk in detecting the tongue region based disease. The detecting of tongue region becomes is being a major and difficult tasks. The region of tongue should be separated and used to detect the disease. There is a error in detecting the disease and while separating the tongue region. In the existing system it is a difficult one to separate the mark region of the tongue. To overcome the issue, In proposed system CNN is used to diagnose disease without any issues or problem in diagnosing. Here the tongue region is separated from the tooth based region and masked tongue used to diagnose the disease. It promises in helping humans to new effective concepts of medical facilitate and reduces the risks in medical field or diagnoses.